Information technology. International standardized profiles FVT2nn. Virtual terminal basic class. Register of control object type definitions. FVT221. Forms FEICO (Field Entry Instruction Control Object) No.1 Part 8, (15th March 1995) - British Standards Institution,
No abstract available